O modernismo em Belo Horizonte: a contribuição de Achilles Vivacqua - Juliana Cristina de Carvalho (2013)
This dissertation intends to study, through a new perspective, the city of Belo Horizonte in the 1920s, the modernism from Minas Gerais, along with the life and works of writer Achilles Vivacqua. Once settled in the state capital, Vivacqua established strong and intimate friendship bonds with great names of Brazilian literature, such as Carlos Drummond deAndrade and Pedro Nava. The tested hypothesis states that even though Achilles Vivacqua is not widely known nowadays, in his time he played an important role in the cultural scenario of Belo Horizonte, as well as in the literature created in Minas Gerais and even Brazil as a whole, actively participating in the Minas Gerais modernist movement. We believe that, ifread and studied, the author may vastly contribute to the understanding of the local modernism, which is, on occasion, limited to a shadow of the movement in São Paulo in literary research. The most important legacy of Achilles Vivacqua is his unique way of dealing with literature. He observed everything around himself, processed it to later show theworld his view, this thoughts, his literature. He did not follow any rule book, he did not religiously follow the ideologies preached by contemporary artists; he would study them and express, in his own way, his understanding of it. Research allows to emphasize the importance of Achilles Vivacqua, his context, his world, his literature, including BeloHorizonte and the modernism from Minas Gerais, also proving the possibility of analysing the movement through non-canonical writers.